571. In a Well-Characterized Cohort with Universal Access to Care and Medications Racial Disparities in HIV Virologic Outcomes Are No Longer Observed. (26th November 2018) - Ganesan, Anuradha; Won, Seunghyun; Joya, Christie; Deiss, Robert; Maves, Ryan; Kronmann, Karl; Lalani, Tahaniyat; Schofield, Christina; Whitman, Timothy J; Okulicz, Jason; Agan, Brian
Abstract: Background: HIV-infected African-Americans [AA] are more likely to experience virologic failure (VF) compared with other ethnic groups. Decreased access to healthcare has been postulated as a potential cause. Using data from the US Military Natural History Study (NHS), we examined the effects of race on VF. The NHS is a longitudinal cohort comprised of Department of Defense (DoD) beneficiaries with unrestricted access to healthcare. Methods: We included NHS participants who contributed follow-up after 2001. Demographic characteristics, antiretroviral therapy (ART) history, and serial viral loads (VL) were obtained from the database. Pharmacy records were used to calculate adherence. VF was defined as a VL of 3 200 copies/mL on two consecutive measurements or one VL of >1, 000 c/mL. A Cox model with time-updated covariates was used to examine the association between race and VF. Results: A total of 1, 521 subjects contributed follow-up after 2001 (41% AA; 95% male). Median age, CD4 count and VL at ART initiation (AI) were 31.6 years [IQR 26–39], 367 cells/μl [IQR 271–489] and 4.6 log10 copies/mL [IQR 4.0–5.0], respectively. Subjects were followed for a median of 4.8 years [IQR 2.7–7.9], and 13.2% ( n = 201) met criteria for VF. Most subjects initiated ART with a non-nucleoside reverse transcriptase inhibitor (NNRTI) (64%), integrase strand transferase inhibitor (InSTI) (15%) or a boosted protease inhibitor (PI) (14%)-based regimen. Results of the adjusted Cox model are in the table below. Conclusion: In the NHS, in recent years, AA and Caucasians have similar responses to ART. NNRTI and InsTI use was protective, reinforcing that simpler medications with fewer adverse effects improve outcomes. Unrestricted access to care and modernization of ART should help narrow the disparities observed in virologic outcomes. Disclosures: All authors: No reported disclosures.